2002
DOI: 10.1080/02726340290083905
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Finite Element Methods for Array and FSS Analysis Using Multiresolution Elements and Fast Integral Techniques

Abstract: Hierarchical mixed-order tangential vector nite elements (TVFEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The shift, in Fig.8 between our results and those of [1] and CST, at low frequencies, is not due to the RC but to the FE spatial discretisation accuracy, i.e. more accurate results are expected if the mesh is refined and higher order elements are employed [21,22]. In [23] (page 392) a similar shift is obtained between two sets of results when modeling a similar structure.…”
Section: Numerical Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The shift, in Fig.8 between our results and those of [1] and CST, at low frequencies, is not due to the RC but to the FE spatial discretisation accuracy, i.e. more accurate results are expected if the mesh is refined and higher order elements are employed [21,22]. In [23] (page 392) a similar shift is obtained between two sets of results when modeling a similar structure.…”
Section: Numerical Resultssupporting
confidence: 64%
“…Furthermore, for a given number of finite elements, more accurate results are obtained by using higher order elements. This is illustrated in references [21,22].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…3) Stage 3: Evaluating at the Actual Observers: The far-field potential at all observers is obtained by interpolating from the potential at the observation grid: (11) where are interpolations coefficients similar to those for the source grid. The computational cost of this stage scales as .…”
Section: Evaluation Of the Far-field Periodic Potentialmentioning
confidence: 99%
“…2) allows using FFTs to accelerate computations in both low-and high-frequency regimes. The choice of uniform grids still allows for a seamless handling of non-uniform source-observer distributions (e.g., in (10) and in (11) can have any distribution).…”
Section: Evaluation Of the Far-field Periodic Potentialmentioning
confidence: 99%
“…(3) Presumptuous that E placates certain frontier conditions on the exterior S that encircles the calculation area V , it can be shown that the unique delinquency is equal to the subsequent variation delinquency [9]: δF(E) = 0 (4) where + exterior integral terms (5) where the exterior integral terms are the outcomes of impressive parallel frontier conditions. This subsection only deliberate on the inner share of the delinquency.…”
mentioning
confidence: 99%